(untitled) (ESMAT Magazine, 2026)
The investigation will make visible the actions and strategies of the Laboratory of Human Rights, Gender and Sexuality (LADIHGES) of the Federal University of Roraima in the areas of gender, sexuality and Human Rights, to sensitize students, teachers and society in Boa Vista about these topics of global relevance. Due to the different cases of violence against women and the LGBT+ community (lesbians, gays, bisexuals, transgenders, etc.) in Boa Vista. As an alternative to the modification of realities, the creation of the Laboratory was implemented to be a reference space for the study of themes related to the episodes of prejudice and discrimination that dominate this location, in the extreme north of the country. With this conflictive situation, the article will present an analytical research structure and will analyze, through the exploratory bibliographic method, the importance of LADIHGES for the sensitization of Roraima society about the themes. The study will seek to answer the following question: How can a Laboratory impact as an agent of change in the contest of disrespect for Human Rights in the state of Roraima? The investigation concludes that there is a need to produce new studies on the theme of this article to foster dialogue in the academic and scientific spheres of issues that deal with Human Rights, gender and sexuality in Boa Vista, since inequalities exclude and social participation people in themes of gender, their identities and sexualities in Roraima.